The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.bone.2016.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Roux-en-Y gastric bypass and sleeve gastrectomy on bone mineral density and marrow adipose tissue

Abstract: Bariatric surgery is associated with bone loss but skeletal consequences may differ between Roux-en-Y gastric bypass (RYGB) and sleeve gastrectomy (SG), the two most commonly performed bariatric procedures. Furthermore, severe weight loss is associated with high marrow adipose tissue (MAT); however, MAT is also increased in visceral adiposity. The purpose of our study was to determine the effects of RYGB and SG on BMD and MAT. We hypothesized that both bariatric procedures would lead to a decrease in BMD and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
139
4
7

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 142 publications
(161 citation statements)
references
References 42 publications
11
139
4
7
Order By: Relevance
“…Others have found no association between change in marrow fat and bone loss in patients undergoing bariatric surgery. (18,19) The degree of bone loss that we report per each SD greater BMAT content is an increased loss of spine trabecular BMD of 0.9 mg/cm 3 /year. Other studies have reported that a difference in spine trabecular vBMD of about −0.04 mg/cm 3 /year is associated with increased risk of nonspine fracture (HR = 1.47), (20) hip fracture (HR = 1.8), and clinical spine fracture (HR = 3.7).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Others have found no association between change in marrow fat and bone loss in patients undergoing bariatric surgery. (18,19) The degree of bone loss that we report per each SD greater BMAT content is an increased loss of spine trabecular BMD of 0.9 mg/cm 3 /year. Other studies have reported that a difference in spine trabecular vBMD of about −0.04 mg/cm 3 /year is associated with increased risk of nonspine fracture (HR = 1.47), (20) hip fracture (HR = 1.8), and clinical spine fracture (HR = 3.7).…”
Section: Discussionmentioning
confidence: 69%
“…Kim and colleagues evaluated changes in vertebral BMAT and bone density in 30 obese women undergoing bariatric surgery, and found that greater increases in marrow fat correlated with greater bone loss at the spine (vBMD) and femoral neck (aBMD). Others have found no association between change in marrow fat and bone loss in patients undergoing bariatric surgery …”
Section: Discussionmentioning
confidence: 96%
“…There may be common metabolic factors that regulate both marrow and visceral fat, just as marrow fat has been associated with intrahepatic and intramyocellular lipids . The positive relationship between the visceral and marrow fat depots has been observed in cross‐sectional studies and a longitudinal study of bariatric surgery, although it was not found in a longitudinal study of dietary weight loss . Thus, the relationship between changes in marrow fat and other fat depots does not appear uniform and may depend on the relative contribution of visceral fat loss.…”
Section: Discussionmentioning
confidence: 99%
“…Two other studies have examined vertebral marrow fat in subgroups of participants who have had RYGB. In 11 people undergoing RYGB, Bredella and colleagues found no significant change in vertebral marrow fat content after 12 months and no relationship between marrow fat and BMD changes . These RYGB participants, 2 of whom had diabetes, were compared with 10 individuals who underwent sleeve gastrectomy, in whom marrow fat content increased.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation